POTENSI WAKAF UANG DALAM SISTEM EKONOMI ISLAM - wing prayuda; wing prayuda; Samud Samud; Samud Samud (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
Waqf is an Islamic social and religious institution that has played an important role in the history of Muslim society. Cash waqf is a solution that can make waqf more productive. The potential for cash waqf in Indonesia is enormous. Management of cash waqf in a professional manner is expected to be able to develop cash waqf and provide benefits for the welfare of the wider community. Therefore there is a need for innovation in the development of cash waqf assets and one of them is by way of investment.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The results of this study are that in practice the management of cash waqf is contained in the form of programs, including: educational programs, social programs, health programs, and economic programs. Cash waqf is a program that is in accordance with Islamic law because in it there are many benefits for mankind both in this world and in the hereafter.Â Keywords: Waqf, Money, and Islamic Economics.